Difference In The Effect Of Giving Trampoline Exercise With Wooble Board Exercise On Increasing Dynamic Stabilization - Astrid Komala Dewi; Catherine Hermawan Salim; Yurita Mailintina (Sean Institute, 2024)
The aim of the research is to determine the difference in the effects of providing trampoline exercise with wooble board exercise on increasing dynamic stabilization. The sample consisted of 20 students at Esa Unggul University and were selected based on random sampling techniques using the available questionnaires. The samples were grouped into two treatment groups, treatment group I consisted of 10 people with trampoline exercise and treatment group II consisted of 10 people who were given wooble board exercise. This research method is a type of quasi-experimental pre-post test design research. Statistical analysis of this research uses the Related T-Test and the Independent T-Test. The results of the homogeneity test for the treatment group before training were with a p value = 0.008. The results of the T-Test Related test in treatment group I have a value of p = 0.001 and in treatment group II the value of p = 0.001 means that the training given to each group has an effect on increasing dynamic stabilization. And the Independent T-Test test results show a p value = 0.001, which means there is a very significant influence between treatment group I and treatment group II. It can be concluded that there is a very significant difference in effect between trampoline exercise and wooble board exercise on increasing dynamic stabilization. In this study, it is recommended that the training method can be applied with the correct procedures, carried out within more than 1 month because with increasing dynamic stabilization the results will be better if carried out within 2-3 months, and it is hoped that things that can influence the results research can be minimized in order to achieve optimal results.